Education as (de)humanization. A possibility for a creative dialogue between the social philosophies of Paulo Freire and Zygmunt Bauman - Tuleikytė, Julija; Jacobsen, Michael Hviid (Studia Krytyczne/Critical Studies, 2023)
This article examines the works of two social critics – Paulo Freire and Zygmunt Bauman – with regard to the idea of education as a cause of dehumanization and/or humanization. The key terms and ideas the authors use in their critique of dehumanization within social relations are compared: Freire’s concept of banking model of pedagogy is analysed in contrast to Bauman’s philosopheme of adiaphorization. With both similar and very different understandings of what it means to be human, the two authors search for alternatives to the status quo and to power relations of human subjects being treated as objects – be it, in Freire’s case, the oppressed in the 20th century Brazil or, in Bauman’s case, the Holocaust victims in the 20th century and persons in the contemporary 21st century consumer society. The article aims at founding the thesis that both authors promote humanization, although in different ways, and that Bauman’s humanization through metaphors is in times of liquid modernity a contemporary form of Freire’s modern critical pedagogy. The article also aims to generally present Bauman’s conception of education as the author so far has been much less introduced in educational sciences than Freire is, and a comparison of their education philosophies reveals how modern and postmodern principles of the two theories and their practical implications complement one another and engage in a possibility for a creative dialogue.